Research Progress of Chimeric Antigen Receptor NK Cells in Treatment of Lymphoma - HU Run; YAO Pei; LI Junen; GUI Renjie; DUAN Huaxin (Zhongliu Fangzhi Yanjiu, 2023)
Adoptive cell immunotherapy has been a hot spot in tumor research in recent years. Chimeric antigen receptor T cells (CAR-T) have achieved great success in hematological tumors and have changed the current tumor treatment landscape to a certain extent. However, the application of CAR-T therapy in clinics is limited due to its serious side effects and high treatment costs. Natural killer (NK) cells are important immune cells in the body and have native cytotoxicity and well safety. NK cells based on CAR engineering (CAR-NK) have shown powerful anti-tumor activity and safety in preclinical research and could be the next generation of CAR platform-based cellular immunotherapy. This review will systematically introduce the current research status of CAR-NK cells in lymphoma.